Aerobic Exercise As a Potential Way to Improve Self-Control after Ego-Depletion in Healthy Female College Students - Zou, Zhiling; Liu, Yang; Xie, Jing; Huang, Xiting (Frontiers in Psychology, 2016)
Purpose: To test whether aerobic exercise can help build self-control stamina in healthy female young adults. Stamina in this context is defined as the capability to endure ego depletion, which can be measured with a self-control task following another activity also requiring self-control. Methods: Forty-five healthy undergraduate women were randomized to either an experimental group or control group. Participants in the experimental group were required to run in their campus running field for 30 min for a period of 5 weeks. Individuals in the control group were required to do diary entries regarding self-control in their daily lives, also for a period of 5 weeks. Before and after the 5-week intervention, participants completed a pain threshold test, a color word Stroop task and the following Cold Pressor Task (CPT) (with and without a distraction component). Results: There was significant decrease of pain tolerance in session 2 relative to session 1 in the control group, but no such decline was found in the experimental group (though the improvement of pain tolerance was not significant), possibly suggesting successful self-control against this kind of decline. Conclusions: Five weeks of aerobic exercise increased self-control after ego depletion in terms of pain tolerance. These findings suggest that aerobic exercise may serve as a potential effective intervention for enhancing self-control in a college female population.